2007
DOI: 10.1136/bjo.2006.099945
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tilt and decentration of scleral-sutured intraocular lens on ocular higher-order wavefront aberration

Abstract: Aim: To investigate the influence of tilt and decentration of scleral-sutured intraocular lenses (IOLs) on ocular higher-order wavefront aberrations. Methods: In 45 eyes of 36 patients who had undergone scleral suture fixation of posterior chamber IOL, tilt and decentration of IOLs were determined by Scheimpflug videophotography, and higher-order aberration for a 4-mm pupil was measured using the Hartmann-Shack aberrometer. In another 100 eyes of 100 patients after standard cataract surgery with posterior cham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 45 publications
4
54
2
Order By: Relevance
“…Discordance between the 2 positions might cause IOL tilting or decentration due to IOL deformity. 13 The conventional method (suturing at the haptic) is usually promising but could produce a gap between the haptic and the sulcus area, leading to IOL tilting in a rare case of ciliary body atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Discordance between the 2 positions might cause IOL tilting or decentration due to IOL deformity. 13 The conventional method (suturing at the haptic) is usually promising but could produce a gap between the haptic and the sulcus area, leading to IOL tilting in a rare case of ciliary body atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies utilizing recent wavefront technology have found that ocular surgeries increase the incidence of ocular and corneal higher order aberrations, thereby affecting postoperative visual function [14][15][16][17][18][19]. Thus, a good understanding of the effect of ocular surgeries on ocular and corneal higher order aberrations is clinically important.…”
Section: Discussionmentioning
confidence: 99%
“…Patients sometimes complain of changes in vision after trabeculectomy, but the mechanisms of these changes are not fully understood. On the other hand, recent advances in wavefront technology have revealed that ocular surgeries, such as corneal transplantation [14][15][16], intraocular lens implantation [17], scleral buckling surgery [18], and pterygium surgery [19], increase ocular and/or corneal higher order aberrations, thereby affecting postoperative visual function. It is thus evident that a thorough understanding of the effect of ocular surgeries on ocular and corneal higher order aberrations is clinically important.…”
Section: Introductionmentioning
confidence: 99%
“…Subjects performed visual acuity tests using these wavefront patterns. The amounts of decentration and tilt chosen for this study were based on Eppig et al, 11 who analyzed clinical studies [25][26][27][28][29][30][31][32][33][34][35] that evaluated IOL decentration and after cataract surgery. The authors found that in general, the mean decentration in the studies was 0.30 G 0.16 mm and the mean tilt was 2.62 G 1.14 degrees.…”
Section: Discussionmentioning
confidence: 99%